The School Inspection in Catalonia. A case study - Patricia Silva García (ADIDE Federación, 2008)
This paper has a twofold purpose: one focused on the research outcomes of School Inspection running in Catalonia and the other centred on some principles for inspector's job strengthening within their professional activities. It is known that tasks develop by inspectors, as support agents, can impact positively at school quality improvement. In other words, beyond educative policy, it is require mechanisms, strategies and resources that can help educative services to strengthen their capacities to promote better and effective professional practices.